High occurrence of CYP3A5 variants among breast cancer and organ transplant patients - Ismail, S; Mohammad, NI; Hamzah, S; Mohamad , R; Harun, R; Suhaimi, S; Jaszle, S; Sood, S; Henry, F; Shabery, A; Rajoo, T; Bahri, R; et al. (2010)
Abstract CYP3A5 is one of the important drug metabolising enzyme and its polymorphism shows marked differences in protein expression and catalytic activities between different geographical ethnic groups. Both tamoxifen and tacrolimus are substrates of CYP3A5 and thus the polymorphism may cause pharmacokinetics variation which explains the wide variaton in the dose requirement and patients’s responses. CYP3A5*3 (A22893G) allele resulted in a truncated protein with loss of CYP3A5 expression whilst the CYP3A5*6 (G 30597A) allele caused deletion of exon 6 from the splice variant and was associated with lower CYP3A5 catalytic activity. Both of these polymorphisms lead to the inability of an individual to express full functional CYP3A5. Aim This study aims to investigate the frequency of CYP3A5 haplotypes among healthy volunteers, breast cancer and kidney transplant patients in selected hospitals. Methods This study was approved by the Medical Research Ethic Committee and local institution. Subjects were screened for inclusion and exclusion criteria and recruited after informed consent. Five ml of blood was obtained from subjected and DNA was extracted and subjected to genotyping of CYP3A5 variants. Multiplex PCR were designed with novel primers specific to 3’ end that amplify the variants of A6986G and G14690A. The optimized method was validated by direct sequencing. Result Twelve breast cancer patients (tamoxifen therapy), 6 organ transplant patients (tacrolimus therapy) and 264 healthy blood donors (98 Malay and Chinese; 74 Indian) were successfully recruited. CYP3A5 is highly polymorphic in the Malaysian populations with the *3 allele having a frequency of more than 60% among the healthy volunteers. The frequency of *3 allele was lower (54.17%) in breast cancer patients. All the 6 patients treated with tacrolimus carry at least one mutated variant (1 patient was heterozygous and 5 were homozygous CYP3A5*3). CYP3A5 *6 allele was absent all patients. Conclusion High percentage of patients and volunteers carry at least one CYP3A5*3 allele and this may be an important genetic contributor to interindividual as well as interethnic differences in the clearance of CYP3A5 substrates. However, we are conducting an on-going study with a larger sample size of the patients to understand the impact of pharmacodiagnostics of drug metabolizing enzyme and drug receptors in local clinical settings.